A taxonomic revision of Stipeae s.l. tribe (Poaceae) in N Africa - Vázquez, Francisco Maria; Márquez, Francisco; García, David; Oualidi, Jalal El (Phytotaxa, 2025)
The revision of the herbarium specimens of the tribe Stipeae and Ampelodesmeae (Poaceae) from North Africa (Algeria, Libya, Morocco and Tunisia) has led to an updated list of 49 taxa. This taxonomic and nomenclatural revision is based on the study of more than 3,500 herbarium sheets, including the types of more than 80% of the available names. The presence of taxa such as Stipa almeriensis, Stipa apertifolia, Stipa bufensis, S. juncea and Piptatherum holciforme subsp. longiglume is confirmed in North Africa. This work proposes: Eight new combinations: Macrochloa gabesensis, Macrochloa gabesensis subsp. kelibiae, Stipa letourneuxii var. ignea, Stipa letourneuxii var. tunetana, Stipellula parviflora var. sandwithii, Stipellula parviflora var. pilosa, Stipellula parviflora var. hoggarensis, Stipellula tibestica. More than 30 new typifications: Ampelodesmos tenax var. microstachys; Arundo bicolor; Arundo mauritanica; Arundo tenax; Milium thomasii; Oryzopsis coerulescens var. grandis; Oryzopsis paradoxa var. leiolemma; Piptatherum coerulescens var. stramineum; Stipa barbata; Stipa barbata var. brevipila; Stipa barbata var. hispánica; Stipa calatajeronensis; Stipa fontanesii; Stipa gigantea; Stipa gigantea f. pubescens; Stipa gigantea var. planifolia; Stipa sect. Leiostipa ser. Leiostipa; Stipa lagascae subsp. normalis var. australis; Stipa lagascae subsp. normalis var. australis f. glabriligulata; Stipa lagascae subsp. normalis var. embergeri; Stipa lagascae subsp. normalis var. oropediorum; Stipa lagascae subsp. normalis var. pubescens f. breviaristata; Stipa lagascae subsp. normalis var. pubescens f. latifolia; Stipa lagascae subsp. normalis var. pubescens f. puberula; Stipa lagascae subsp. normalis var. trabutii; Stipa lagascae var. malvana; Stipa letourneuxii; Stipa nitens; Stipa offneri; Stipa parviflora subsp. sinaica and Stipa plumosa. One new species: Stipa trabutiana sp. nov. One new series within the Stipa genus: Stipa sect. Leiostipa ser. Africanae ser. nov. A detailed morphological description (with 19 reproductive characters) is provided for all taxa, as well as illustrations, distribution maps, and information on ecology. Clarification is provided for taxa whose systematics and/or nomenclature remain unclear. In addition, the micromorphology of the lemma surface was examined by scanning electron microscopy (hereafter SEM) for many taxa (specimens from ECWP, HSS and RAB). Those results are the first to be published for over 80% of the taxa studied. These results confirm previous taxonomic works and provide an additional tool for taxonomic studies. For the first time, the presence of stomata in the lemma of Stipeae is illustrated, as well as prickles and hooks, and the variation in the morphology of long and short cells. Our taxonomic proposals were compared with a cluster analysis (degree of similarity) of the macromorphological and micromorphological characters of the lemma. The results confirm over 95% of our taxonomic and nomenclatural proposals. Identification keys are provided for all genera and taxa.